Treatment efficacy for infantile epileptic spasms syndrome in children with trisomy 21 - Chen, Henry; Numis, Adam L.; Shellhaas, Renée A.; Mytinger, John R.; Samanta, Debopam; Singh, Rani K.; Hussain, Shaun A.; Takacs, Danielle; Knupp, Kelly G.; Shao, Li-Rong; Stafstrom, Carl E. (Frontiers in Pediatrics, 2025)
BackgroundInfantile Epileptic Spasms Syndrome (IESS) is the most common epilepsy syndrome in children with trisomy 21. First-line standard treatments for IESS include adrenocorticotropic hormone (ACTH), oral corticosteroids, and vigabatrin. Among children with trisomy 21 and IESS, treatment with ACTH or oral corticosteroids may yield higher response rates compared with vigabatrin. However, supporting data are largely from single-center, retrospective cohort studies.MethodsLeveraging the multi-center, prospective National Infantile Spasms Consortium (NISC) database, we evaluated the efficacy of first-line (standard) treatments for IESS in children with trisomy 21. We assessed clinical spasms remission at two weeks, clinical spasms remission at three months, and improvement of EEG (resolution of hypsarrhythmia) three months after initiation of treatment.ResultsThirty four of 644 (5.3%) children with IESS were diagnosed with trisomy 21. In all children with trisomy 21, epileptic spasms was their presenting seizure type. Twenty of 34 (59%) children were initially treated with ACTH, nine (26%) with oral corticosteroids, and five (15%) with vigabatrin. Baseline demographics did not vary among treatment groups. The overall clinical remission rate after two weeks of treatment was 53% including 13 of 20 (65%) receiving ACTH, three of nine (33%) receiving oral corticosteroids, and two of five (40%) receiving vigabatrin (p = 0.24). The continued clinical response rate at three months was 32% including 8 of 20 (40%) receiving ACTH, two of nine (22%) receiving oral corticosteroids, and one of five (20%) receiving vigabatrin. Thirty of the 34 (88%) children presented with hypsarrhythmia (88%). EEG improvement at three months was better for children treated with ACTH (74%) or oral corticosteroids (83%) than vigabatrin (20%; p = 0.048). Adjustment for time from epileptic spasms onset to treatment did not alter results.ConclusionsIn our cohort, epileptic spasms were the first presenting seizure type in all children with trisomy 21. Among first-line standard treatment options, ACTH may have superior efficacy for clinical and electrographic outcomes for IESS in children with trisomy 21.